‘Konstige tanden’. Gebitsprothesen van bot en ivoor in Nederlandse collecties - Rijkelijkhuizen, Marloes; de Raat, Reina (Studium, 2016)
‘Konstige tanden’ – False teeth made of bone and ivory from Dutch collectionsDental healthcare in the past was not as advanced as nowadays. Most people who suffered from caries (or worse) had no other option than to have the ‘bad’ tooth extracted. A set of false teeth was only an option the rich could afford. Finding a suitable material for these prostheses was a struggle for the manufacturers. For a long period ivory, and sometimes bone, was the only option.The aim of this study was to examine more than one hundred false teeth made of bone and ivory from archaeological and museum collections, with the purpose to identify the used materials and to investigate the development of these dentures. Archaeological examples were the oldest false teeth recovered, the oldest dating to the 17th century.A persistent misinterpretation is the use of walrus ivory for the manufacture of false teeth in the time under investigation. Both walrus and hippopotamus ivory have been misidentified for a long time mainly because both species have been named ‘seahorse’. Of all the examined dentures 71% was made of hippopotamus ivory, 18% of walrus ivory, 8% of elephant ivory and only 3% of bone. Before the discovery of vulcanised rubber in the mid-19th century hippopotamus ivory was the best material to manufacture false teeth, because of the hard enamel layer which retained its white colour much longer than other materials. Archaeological finds show that hippopotamus ivory was imported for only one purpose: the manufacture of false teeth.These false teeth were probably made more often by ivory workers rather than by ‘tooth masters’. Although ivory false teeth were a good solution for esthetical reasons and to regain speech and chewing abilities, the lack of hygiene must have caused a lot of pain and trouble to their rich wearers.